A Case of Suspected Adverse Reactions to Sirolimus in the Treatment of Generalized Lymphatic Anomaly - Takayuki Fujii; Ryuichi Shimono; Aya Tanaka; Hiroto Katami (Hindawi Limited, 2019)
Generalized lymphatic anomaly (GLA) is characterized by diffuse or multicentric proliferation of dilated lymphatic vessels resembling common lymphatic malformation, and thoracic lesions can be related to a poor prognosis. Sirolimus, an inhibitor of the mammalian target of rapamycin, is effective against vascular anomalies with few severe adverse drug reactions. Here, we report the case of a patient with intractable hemothorax pleural effusion due to GLA who was treated with sirolimus and experienced disseminated intravascular coagulation. Although a standard treatment for GLA has not been established, pleural fluid might be reduced using the Kampo medicine Eppikajyutsuto.